ANALISI PUTUSAN NOMOR 959/Pdt.P/2020/PN. Bdg. TENTANG PERKAWINAN BEDA AGAMAANALISI PUTUSAN NOMOR 959/Pdt.P/2020/PN. Bdg. TENTANG PERKAWINAN BEDA AGAMA - Berlian Ananda; Rizki Rizki; Dandi Bangun (UNES Law Review, 2022)
Basically, humans were created to live in pairs or to marry, namely men and women. In Indonesia there are various ethnic groups, races and religions. These differences will affect the marriage between men and women that will be carried out. In fact, it has become a common thing if there are parties who carry out interfaith marriages. The rules regarding marriage are regulated in Law no. 1 of 1974 concerning Marriage. However, these regulations are not explicitly regulated regarding marriages of different religions. The purpose of this study is to understand the arrangement of judges in interfaith marriages, understand the judge's considerations in the decision Number 959/Pdt.P/2020/PN. cf. and to understand the legal consequences that will occur. This research uses a normative juridical system. The data sources used are secondary data by processing data from primary legal materials and secondary legal materials. In the form of laws, books on civil procedural law, opinions of legal experts and theses. The results of this study are interfaith marriages which are recognized by state law if they carry out civil registration, contained in Article 37 of the Law on Population Administration, but are not legal according to religion. Parties of different religions cannot carry out marriages based on the ordinance of religious marriages, there are religious differences.